Sử dụng hình mẫu khuyết và Entropy hoán vị để kiểm định tính hiệu quả thông tin trên thị trường chứng khoán của các quốc gia ASEAN - Trần Thị Tuấn , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
his study applies the method proposed by Bandt and Pompe (2002) to daily stock index series collected from six ASEAN countries including Philippines, Vietnam, Malaysia, Indonesia, Thailand, and Singapore over the period 01/2000–11/2018 to look for the existence of a forbidden pattern and to calculate normalized permutation Entropy. The research results show that there exists a forbidden pattern in all 6 stock markets. The probability of different permutation patterns is also different. These are evidence for inefficient markets. Additionally, the result of computed normalized permutation Entropy using on stock index series also demonstrates the inefficiency of the market when this value does not reach its maximum value. This article also suggests that using a series of stock index will help to find evidence of an inefficient market much more powerful than using a series of market returns.